Effects of Tryptophan on the Polymorphic Transformation of Calcium Carbonate: Central Composite Design, Characterization, Kinetics, and Thermodynamics - SAYAN, PERVİZ; POLAT, SEVGİ (SLOVENSKO KEMIJSKO DRUSTVO, 2021)
The objectives of this study were to: (i) determine the effects of tryptophan on the polymorphic phase transformation of CaCO3, (ii) investigate the thermal degradation characteristics of CaCO3 in terms of kinetics and thermodynamics using the Coats-Redfern method, and (iii) assess the influence of the experimental conditions on the vaterite composition of CaCO3 using response surface methodology based on central composite design. First, the CaCO3 crystals were prepared and analyzed using XRD, FTIR, SEM, BET, AFM, and zeta potential analysis. Based on the characterization results, the shape of the CaCO3 crystals changed from smooth cubic calcite crystals to porous irregular spherical-like vaterite crystals with increasing tryptophan concentration. Meanwhile, the kinetic results showed that the thermal degradation of CaCO3 followed the shrinkage geometrical spherical mechanism, R-3 and the average activation energy was 224.6 kJ/mol. According to the results of the experimental design, the tryptophan concentration was the most influential variable affecting the relative fraction of vaterite in the produced crystals. It can be concluded that tryptophan is important for better understanding and controlling the polymorph, size, and morphology of CaCO3 crystals.
Keywords: Calcium carbonate; polymorphism; central composite design; kinetics; thermodynamics; THERMAL-DECOMPOSITION; CRYSTALLIZATION; PRECIPITATION; PARAMETERS